2020
DOI: 10.1002/aisy.201900190
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Contact Lens: A Platform for Wireless Health Monitoring Applications

Abstract: Electronic contact lenses are used for noninvasively monitoring vital human signs and medical parameters. However, maintaining a secure communications connection and a self‐sustainable power source are still looming challenges. Herein, a proof‐of‐concept electronic contact lens is demonstrated that includes a spiral antenna with its wireless circuit unit for data telemetry, a rectifier circuit for power conditioning, and a micro‐light‐emitting diode (μLED) as a load. The spiral antenna with its rectifying circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Wireless powering is one of the heavily applied technical areas of microwave flexible electronics, having demonstrated its important utility in implantable devices where conventional conductive wires were not preferred. [32,35,210,265] By encapsulating a stretchable antenna and rigid Schottky diodes-based rectifier in stretchable elastomer, a fully implantable optoelectronic systems with wireless powering at 2.34 GHz has been demonstrated (Figure 10c). [210] Chiou et al also reported wireless powering and data transmission systems by integrating rigid sensor readout circuit, analog/RF front end and digital processors with flexible antenna and flexible sensors to monitor intraocular pressure.…”
Section: Flexible and Stretchable Microwave Electronic Systemsmentioning
confidence: 99%
“…Wireless powering is one of the heavily applied technical areas of microwave flexible electronics, having demonstrated its important utility in implantable devices where conventional conductive wires were not preferred. [32,35,210,265] By encapsulating a stretchable antenna and rigid Schottky diodes-based rectifier in stretchable elastomer, a fully implantable optoelectronic systems with wireless powering at 2.34 GHz has been demonstrated (Figure 10c). [210] Chiou et al also reported wireless powering and data transmission systems by integrating rigid sensor readout circuit, analog/RF front end and digital processors with flexible antenna and flexible sensors to monitor intraocular pressure.…”
Section: Flexible and Stretchable Microwave Electronic Systemsmentioning
confidence: 99%
“…Smart CLs are wearable devices for health monitoring, sensing, or diagnostic capabilities. [ 15,16,98–101 ] Recently, smart CLs are extensively studied to continuously monitor vital signs from ocular conditions (e.g., dry eye, glaucoma) to monitor diseases such as diabetes [ 98,102–107 ] as well as physiological level of pH. [ 102,108 ] Figure shows examples of the smart CLs.…”
Section: Smart Clsmentioning
confidence: 99%
“…An exposure time of 15 mins provided the best results when using 100% infill from the PolySmooth TM filament. The smoothness of the mould increases with an increased exposure time, but overexposure may cause its dimensions to alter, since the 3D-printed mould was based on the eye's real curvature, over-exposure will degrade the contact lens' wearability [39]. Use of 3D moulds has been reported in the literature, and the rough surfaces resulting from 3D-printing found to be problematic [40], causing user discomfort due to friction from the contact lens surface [41].…”
Section: Contact Lens Fabricationmentioning
confidence: 99%